Endoscopic versus percutaneous biliary drainage in patients with resectable perihilar cholangiocarcinoma: a multicentre, randomised controlled trial. (October 2018) - Coelen, Robert J S; Roos, Eva; Wiggers, Jimme K; Besselink, Marc G; Buis, Carlijn I; Busch, Olivier R C; Dejong, Cornelis H C; van Delden, Otto M; van Eijck, Casper H J; Fockens, Paul; Gouma, Dirk J; Koerkamp, Bas Groot; et al.
Summary: Background: In patients with resectable perihilar cholangiocarcinoma, biliary drainage is recommended to treat obstructive jaundice and optimise the clinical condition before liver resection. Little evidence exists on the preferred initial method of biliary drainage. We therefore investigated the incidence of severe drainage-related complications of endoscopic biliary drainage or percutaneous transhepatic biliary drainage in patients with potentially resectable perihilar cholangiocarcinoma. Methods: We did a multicentre, randomised controlled trial at four academic centres in the Netherlands. Patients who were aged at least 18 years with potentially resectable perihilar cholangiocarcinoma requiring major liver resection, and biliary obstruction of the future liver remnant (defined as a bilirubin concentration of >50 μmol/L [2·9 mg/dL]), were randomly assigned (1:1) to receive endoscopic biliary drainage or percutaneous transhepatic biliary drainage through the use of computer-generated allocation. Randomisation, done by the trial coordinator, was stratified for previous (attempted) biliary drainage, the extent of bile duct involvement, and enrolling centre. Patients were enrolled by clinicians of the participating centres. The primary outcome was the number of severe complications between randomisation and surgery in the intention-to-treat population. The trial was registered at the Netherlands National Trial Register, number NTR4243. Findings: From Sept 26, 2013, to April 29, 2016, 261 patients were screened for participation, and 54 eligible patients were randomly assigned to endoscopic biliary drainage (n=27) or percutaneous transhepatic biliary drainage (n=27). The study was prematurely closed because of higher mortality in the percutaneous transhepatic biliary drainage group (11 [41%] of 27 patients) than in the endoscopic biliary drainage group (three [11%] of 27 patients; relative risk 3·67, 95% CI 1·15–11·69; p=0·03). Three of the 11 deaths among patients in the percutaneous transhepatic biliary drainage group occurred before surgery. The proportion of patients with severe preoperative drainage-related complications was similar between the groups (17 [63%] patients in the percutaneous transhepatic biliary drainage group vs 18 [67%] in the endoscopic biliary drainage group; relative risk 0·94, 95% CI 0·64–1·40). 16 (59%) patients in the percutaneous transhepatic biliary drainage group and ten (37%) patients in the endoscopic biliary drainage group developed preoperative cholangitis (p=0·1). 15 (56%) patients required additional percutaneous transhepatic biliary drainage after endoscopic biliary drainage, whereas only one (4%) patient required endoscopic biliary drainage after percutaneous transhepatic biliary drainage. Interpretation: The study was prematurely stopped because of higher all-cause mortality in the percutaneous transhepatic biliary drainage group. Post-drainage complications were similar between groups, but the data should be interpreted with caution because of the small sample size. The results call for further prospective studies and reconsideration of indications and strategy towards biliary drainage in this complex disease. Funding: Dutch Cancer Foundation.